Small Toxic Proteins and the Antisense RNAs That Repress Them - Fozo, Elizabeth M. (American Society for Microbiology (ASM), 2008)
Summary: There has been a great expansion in the number of small regulatory RNAs identified in bacteria. Some of these small RNAs repress the synthesis of potentially toxic proteins. Generally the toxin proteins are hydrophobic and less than 60 amino acids in length, and the corresponding antitoxin small RNA genes are antisense to the toxin genes or share long stretches of complementarity with the target mRNAs. Given their short length, only a limited number of these type I toxin-antitoxin loci have been identified, but it is predicted that many remain to be found. Already their characterization has given insights into regulation by small RNAs, has suggested functions for the small toxic proteins at the cell membrane, and has led to practical applications for some of the type I toxin-antitoxin loci.